Changes in testing and incidence of Chlamydia trachomatis and Neisseria gonorrhoeae – the possible impact of the COVID-19 pandemic in the three Scandinavian countries. Issue 9 (2nd September 2022) - Ivarsson, Lovisa; de Arriba Sánchez de la Campa, Magdalena; Elfving, Karin; Yin, Hong; Gullsby, Karolina; Stark, Lisa; Andersen, Berit; Hoffmann, Steen; Gylfe, Åsa; Unemo, Magnus; Herrmann, Björn
Abstract: Background: This study aimed to investigate what impact the COVID-19 pandemic and its associated restrictions had on Chlamydia trachomatis and Neisseria gonorrhoeae infections in Sweden, Denmark and Norway, countries with very different governmental strategies for handling this pandemic. Methods: Retrospective analysis of data collected via requests to Swedish regions and to health authorities in Denmark and Norway. The data were collected for the years 2018–2020 and the data from Sweden were more detailed. Results: When the pandemic restrictions were installed in 2020, the number of reported chlamydia cases decreased. The decline was most pronounced in Norway 10.8% (2019: n = 28, 446; 2020: n = 25, 444) while it was only 3.1% in Denmark (2019: n = 35, 688; 2020: n = 34, 689) and 4.3% in Sweden (2019: n = 34, 726; 2020: n = 33, 339). Nucleic acid amplifications tests for chlamydia decreased in Sweden (10%) and Norway (18%) in 2020 compared to 2019, while in Denmark a 21% decrease was noted in April 2020 but thereafter increased to a higher level than 2019. The number of reported gonorrhoea cases decreased in Sweden (17%) and in Norway (39%) in 2020 compared to 2019, while a 21% increase was noted in Denmark. Conclusions: Pandemic restrictions had an impact on the number of reported chlamydia infections in all three countries, but only temporarily and did not seem to be correlated to the restriction levels. The number of reported gonorrhoea infections in Sweden and Norway significantly decreased but not in Denmark. Pandemic restrictions appear to have had a limited effect on the spread of chlamydia and gonorrhoea.